PEMILIHAN DAN PEMBENTUKAN PORTOFOLIO SAHAM LQ45 YANG OPTIMAL (STUDI KASUS DI BURSA EFEK INDONESIA (BEI) - Desy Wahyuningrum (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
This article aims to identify how investor choose and decide an optimal portfolio ofstock, using Markowitz and Single Index Model. The analysis on 45 Shares in thegroup of LQ45 in Indonesia Stock Exchange (IDX), found that the optimal portfoliowould be composed of 11 share: TRUB (Truba Alam Manunggal Engineering Tbk),BUMI (Bumi Resources Tbk), TINS (Timah Tbk ), BNBR (Bakrie & Brothers Tbk),BBNI (Bank Negara Indonesia Tbk), and ELTY (Bakrieland Development Tbk). As acomparison of risk and return of optimal and non-optimal portfolio, the optimalportfolio had 14.6% return and 1.6% risk, while the non-optimal had only 7.8% re-turn and 0.13% risk.Keywords: Markowitz Model, Single Index Model, LQ45, Indonesia Stock Exchange,optimal portfolio, risk, return